(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The work of people towards a company represents rights and duties, but it should also be considered as a retribution of comfort and delivery in two ways so that both parties consider a fair treatment and meet the needs. This is why one of the indispensable factors in a work environment is to have a good working environment, adjustments, training, recognition and benefits that are part of the emotional salary that complements the economic compensation. Therefore, being a company recognized or certified nationally by GPTW generates an attraction in the market of personnel, better trained and with more developed skills and aptitudes for a more effective and efficient work, but is it really a company that internally generates satisfaction or sense of belonging in its collaborators?